2009
DOI: 10.1111/j.1475-5890.2009.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Innovations in Collecting Spending Data: The HRS Consumption and Activities Mail Survey*

Abstract: It has traditionally been believed that collecting survey measures of total spending necessarily involved asking a large number of questions, too many for inclusion of a comprehensive spending measure in a general-purpose survey. In this paper, we report on a supplemental survey to the Health and Retirement Study that took up this challenge. We discuss issues that arise when designing a survey module to collect spending data with strict time constraints, describe how the implementation in the Consumption and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 7 publications
(4 reference statements)
1
31
0
Order By: Relevance
“…Issues may arise due to respondents' poor recall or rounding errors, or because the stigma associated with certain financial information makes respondents reluctant to report it. The statistics literature shows that survey responses are highly sensitive to the questionnaire design (Sudman, Bradburn, and Schwarz 1996;Tourangeau, Rasinski, and Bradburn 1991), and that survey-based statistics are very sensitive to the recall period used in the survey questionnaire (Deaton and Grosh 2000;Hurd and Rohwedder 2009). Also, respondents might not know about other household members' financial information for jointly held accounts, or when bills are paid on behalf of the household by another person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Issues may arise due to respondents' poor recall or rounding errors, or because the stigma associated with certain financial information makes respondents reluctant to report it. The statistics literature shows that survey responses are highly sensitive to the questionnaire design (Sudman, Bradburn, and Schwarz 1996;Tourangeau, Rasinski, and Bradburn 1991), and that survey-based statistics are very sensitive to the recall period used in the survey questionnaire (Deaton and Grosh 2000;Hurd and Rohwedder 2009). Also, respondents might not know about other household members' financial information for jointly held accounts, or when bills are paid on behalf of the household by another person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, food spending is often reported as weekly spending whereas rent is often reported as monthly spending. Spending is annualized to produce an estimate of total annual spending (Hurd and Rohwedder, 2009). …”
Section: Datamentioning
confidence: 99%
“…Hurd and Rohwedder (2009) discuss the details of various design elements of CAMS and comparisons of the first four waves of CAMS with CEX spending are presented in Hurd and Rohwedder (forthcoming). They find that in the age range 55–64 CAMS spending was 4% higher than CEX spending on average.…”
Section: Datamentioning
confidence: 99%
“…19 Figure 3 shows that even though the share of total income remaining after OOP costs is larger than the share of OASI income remaining, medical spending takes a large toll on Moreover, the high level of spending on premiums for RHI enrollees may be reported with error. Appendix Figure C shows the analogous results for the CAMS, which prior studies have found to better match other measures of spending more broadly (Hurd and Rohwedder 2008 Figures 5 to 7 show results by these subgroups. Figure 5 shows that for women, the post-OOP OASI ratio is 62 percent, compared with 70 percent for men.…”
Section: Results For the Full Samplementioning
confidence: 73%